Winning basketball fundamentals - Rose, Lee H; Rose, Lee H. (Champaign, IL Human Kinetics, 2013)
Lee Rose has developed hundreds of players at the high school, collegiate, and professional levels throughout his 50-year coaching career. He shares his knowledge of the game in Winning Basketball Fundamentals with offensive and defensive strategies, individual and team drills, and a valuable player evaluation system to help guide coaching efforts.
1. Six guiding principles -- 2. Playing and coaching -- 3. Performance rating system -- 4. Individual offensive skills -- 5. Offensive priorities -- 6. Team offense -- 7. Defensive skills and tactics -- 8. Team defense -- 9. Tactics for special situations.
Revised edition of: The basketball handbook, c2004.
"Includes the game's premier Performance Rating System"--Cover.
Includes index.
Keywords: Basketball -- Coaching -- Handbooks, manuals, etc; Basketball -- Training